1987
DOI: 10.1007/bf02542016
|View full text |Cite
|
Sign up to set email alerts
|

Alkyl ethoxylates: An assessment of their oral safety alone and in mixtures

Abstract: Some alkyl ethoxylates (AEs), nonionic surfactants which are widely used in industry and in household cleaning products, have been demonstrated to produce acute neuropharmacologic effects when sufficient systemic exposure is achieved. An investigative program was undertaken to characterize these effects and to evaluate the neuropharmacologic potential of some AEs with specific chainlengths, both commercially available materials and a pure homologue, following accidental oral exposure. Results show that even th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…The primary ingredient of anionic detergents is ethoxylated alcohol, and ingestions are expected to cause gastrointestinal irritation, such as vomiting (16). While many of the children in this series had multiple episodes of emesis before presentation, all episodes had largely resolved by the time the patients were evaluated in the ED.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The primary ingredient of anionic detergents is ethoxylated alcohol, and ingestions are expected to cause gastrointestinal irritation, such as vomiting (16). While many of the children in this series had multiple episodes of emesis before presentation, all episodes had largely resolved by the time the patients were evaluated in the ED.…”
Section: Discussionmentioning
confidence: 90%
“…Only 6 patients received an anti-emetic and none of those received an intravenous fluid bolus. Animal studies have demonstrated lethargy and ataxia with high oral doses and the degree of ethoxylation is believed to correlate with toxicity (16,17). There has also been speculation that propylene glycol may be responsible for the observed CNS depression, but this seems unlikely given the amounts contained in these products.…”
Section: Discussionmentioning
confidence: 99%
“…Although citric acid could potentially contribute to the reported features, it is typically present in rinse aids at concentrations 5% and therefore the features are more likely to be due to the surfactants. Some non-ionic surfactants, such as ethoxylated alcohols, have been shown to induce ataxia, loss of righting, respiratory depression, coma and death when administered intraperitoneally to rats, 6 although this exposure route may limit the relevance of these observations to human ingestion. Oral administration of non-ionic surfactants to rats and mice, either alone or in combination with anionic surfactants and ethanol, has caused sedation but only following the administration of large volumes of highly concentrated solutions.…”
Section: Discussionmentioning
confidence: 99%
“…Oral administration of non-ionic surfactants to rats and mice, either alone or in combination with anionic surfactants and ethanol, has caused sedation but only following the administration of large volumes of highly concentrated solutions. 6 The length of the alkyl chain does not appear to affect the toxicity of ethoxylated alcohols, although the degree of ethoxylation does. Compounds with ethylene oxide units between 5 and 14 are more toxic orally than those with less than 4 or more than 21 ethoxy units.…”
Section: Discussionmentioning
confidence: 99%
“…A rat study demonstrated sedation effects from some alkyl ethoxylates, but the dose was relatively large; this does raise the possibility of a specific alkyl/ethoxylate chain length that causes significant sedation in humans beyond the general sedative effects of alcohols. 10 Recognition of the severe morbidity from laundry ''pod'' exposures resulted in a change in perception of the product's safety. Despite the European experience, there were no preparations for poison center surveillance or readiness with product codes when introduced to the US market.…”
Section: Discussionmentioning
confidence: 99%